2016
DOI: 10.1108/jrme-06-2015-0033
|View full text |Cite
|
Sign up to set email alerts
|

The impact of market orientation and learning orientation on organisational performance

Abstract: Purpose This study aims to consider the impact of market orientation and learning orientation on organisational performance in the context of small- and medium-sized enterprises (SMEs) in Cape Town, South Africa. SMEs play a vital role in developing countries’ economies given their large contribution towards employment and the economic output (gross domestic product). However, many SMEs struggle to implement practices that are used to successful ends by their corporate counterparts. In view of this, this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
2
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 80 publications
(142 reference statements)
2
48
2
9
Order By: Relevance
“…In contrast to other studies in the developed countries, Beneke et al. () found that LO had neither a significant effect on organizational performance nor a moderating effect on the relationship between market orientation and organizational performance of small‐ to medium‐sized enterprises in South Africa. Besides these divergent results about the moderation effect of LO, another issue that deserves attention is its interaction with strategic HR practices, since both LO and HPWS have influence on individual behavior from the HR perspective (Gong, Huang and Farh ; Jiang et al.…”
Section: Literature Review and Hypothesesmentioning
confidence: 65%
See 3 more Smart Citations
“…In contrast to other studies in the developed countries, Beneke et al. () found that LO had neither a significant effect on organizational performance nor a moderating effect on the relationship between market orientation and organizational performance of small‐ to medium‐sized enterprises in South Africa. Besides these divergent results about the moderation effect of LO, another issue that deserves attention is its interaction with strategic HR practices, since both LO and HPWS have influence on individual behavior from the HR perspective (Gong, Huang and Farh ; Jiang et al.…”
Section: Literature Review and Hypothesesmentioning
confidence: 65%
“…Some of the studies have focused on the direct effect of LO on organizational performance and found a positive relationship between them (Abdulai Mahmoud and Yusif ; Baker and Sinkula ; Beneke et al. ; Calantone, Cavusgil and Zhao ; Mavondo, Chimhanzi and Stewart ). For example, Abdulai Mahmoud and Yusif () investigated the effect of LO in non‐profit organizations and found that LO was positively related to economic and non‐economic organizational performance – specifically, non‐economic performance was the mediator in the relationship between LO and economic performance.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Bakar et al (2016) argue that understanding the environment a firm operates in through the learning orientation enables the business to exploit opportunities as they arise while at the same time working on minimising the threats beforehand. Beneke et al (2016) remark that adopting learning orientation allows a firm to meet and surpass customer expectations. On that note, Haryanto, Haryono and Sawitri (2017) assert that an organisation which embrace learning orientation has a high probability of becoming a market leader.Given the fact that customers in the 21 1 st century are becoming so knowledgeable about the products they buy and make comparisons before they buy, it is important for SMEs to utilise learning orientation to constantly meet their customer needs and remain profitable.…”
Section: Introductionmentioning
confidence: 99%